Elevated serum LDL-C increases the risk of Lewy body dementia: a two-sample mendelian randomization study - Pengdi Liu; Jin Liu; Yafei Zhang; Xin Xing; Le Zhou; Jianqiang Qu; Xianxia Yan (Lipids in Health and Disease, 2024)
Abstract Background Lewy body dementia (LBD) ranks second among prevalent neurodegenerative dementias. Previous studies have revealed associations of serum lipid measures with several neurodegenerative diseases. Nevertheless, the potential connection between serum lipids and LBD remains undetermined. In this study, Mendelian randomization (MR) analyses were carried out to assess the causal relationships of several serum lipid measures with the risk of developing LBD. Methods Genome-wide association study (GWAS) data for serum lipids and LBD in European descent individuals were acquired from publicly available genetic summary data. A series of filtering procedures were conducted to identify the genetic variant candidates that are related to serum lipids, including high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and triglycerides (TG). The causal effects were primarily determined through inverse-variance weighting (IVW)-based analyses. Results Neither TG (odds ratio [OR] = 1.149; 95% confidence interval [CI], 0.887–1.489; P = 0.293) nor HDL-C (OR = 0.864; 95% CI, 0.718–1.041; P = 0.124) had causal effects on LBD. However, a causal relationship was identified between LDL-C and LBD (OR = 1.343; 95% CI, 1.094–1.649; P = 0.005), which remained significant (OR = 1.237; 95% CI, 1.015–1.508; P = 0.035) following adjustment for HDL-C and TG in multivariable MR. Conclusions Elevated serum LDL-C increases the risk of LBD, while HDL-C and TG have no significant causal effects on LBD.